The politics of peacekeeping in Southern Africa: a critical assessment of South Africa's engagement in regional peacekeeping initiatives - Khobotlo, Shadrack Motlalepula (Rhodes University, Faculty of Humanities, Department of Political Studies, 1998)
International peacekeeping has gained a high profile in international relations and more so, in the post cold war era. The profound increase in the occurrence of civil wars globally and the consequent high demand for the UN to intervene has compelled the world body to delegate its peacekeeping powers to regional organisations. SADC is one of many regional organisations around the world which are faced with the challenge of developing peacekeeping capacities to resolve local conflicts. This thesis endeavours to investigate the prospects of peacekeeping in Southern Africa with specific reference to the involvement of South Africa as a regional power with the wherewithal to play a leadership role in this regard. This is done within the theoretical framework that is provided by the Realist school of thought in international relations. Furthermore, the concept of national interest as defined by Realism will be utilised to explain why countries in Southern Africa in general and South Africa in particular become involved in regional peacekeeping initiatives. The issue of whether the Republic should be involved and how much it should be involved has provoked an intense debate within the country. This debate will therefore be instructive in understanding the dynamics that influence the country's foreign policy behaviour towards the region in relation to playing a leadership role in regional peacekeeping initiatives. The central issue implicit in the debate is the fact that most of the SADC member states that are expected to contribute towards these initiatives have weak economies. This economic weakness in turn leads to the thorny issue of having to seek foreign assistance from western countries from which the region is trying to gain greater independence. This presents the region with a paradox because foreign assistance has serious implications for the SADC countries' sovereignty. It is in this context therefore, that this thesis examines economic development in individual SADC countries and in the region as a whole to establish whether they are in a position to develop a sustainable regional peacekeeping capacity. The contention of the thesis is that economic development is closely related to peacekeeping because without a sound economic base Southern Africa or any other region for that matter, will not be able to develop a viable peacekeeping capacity. On the other hand, keeping the peace in the region is itself important for economic development because it is only in a peaceful environment that economic development can take root.
Keywords: Conflict management -- Africa, Southern|National security -- Africa, Southern|Political stability -- Africa, Southern|Africa, Southern -- Politics and government